EL MIEDO A LA CONSULTA EN LOS ADULTOS QUE ASISTEN A LAS CLÍNICAS ODONTOLÓGICAS DE LA UNIVERSIDAD SANTO TOMÁS (2012)
Objective: to assess the relation between fear to dental treatment and the nonattendance to the appointments in adults who assist to the dental clinics at Santo Tomas University in the city of Floridablanca (Santander).Methods: a cross sectional study was done. It included 110 adult people, both genders who attended the dental clinics from January to October 2008. Chi2 test and Fisher’s exact text were used. An alpha value of 0.05 was considered.Results: the percentage of people with fear to dental attendance was 48.2%, 55.6% of women felt fear to their dentist and 28.2% of the population reported having ever missed dental appointments for the fear that this will generate. The syringe of anesthesia as an instrument and endodontics as a specialty had a significant relationship with the dental fear.Conclusions: there was a relationship between fear to dental attendance and non-attendance at appointments by adults. An unpleasant experience was an etiological factor to consider fear to the consultation, as well as their perception of other people about the appearance of the patient’s teeth.